222k views
2 votes
Simplify ----2√45 + 3√3 + 2√3 A~ --18√5 + 5√3 B~ --6√5 + 6√3 C~ --2√5 + 6√3 D~ --6√5 + 5√3

User Fragan
by
5.7k points

2 Answers

5 votes

Answer:

Simplify ----2√45 + 3√3 + 2√3

A~ --18√5 + 5√3

B~ --6√5 + 6√3

C~ --2√5 + 6√3

D~ --6√5 + 5√3

Explanation:

[tex]-2\sqrt{45}+3\sqrt{3} +2\sqrt{3} =-2\sqrt{45} + 5\sqrt{3} =-6\sqrt{5} + 5\sqrt{3}[/tex

User Creaktive
by
5.5k points
1 vote

Answer:

It's D. 6√5 + 5√3 .

Explanation:

2√45 + 3√3 + 2√3

= 2√(9 * 5) + 5√3

= 2 √9√5 + 5√3

= 6√5 + 5√3 (answer).

User Jared Menard
by
5.2k points